Schizophrenia, bipolar disorder, or intracranial aneurysm? A case report - Yifan Shi; Yezhou Tang; Zhiguo Wu; Jun Chen; Jia Huang; Yiru Fang (Brain and Behavior, 2021)
Abstract Background Mental disorders are a common finding among patients with unruptured intracranial aneurysms. Case The current case concerns a young man with an anterior communicating artery aneurysm who was misdiagnosed with schizophrenia and bipolar disorder due to his significant psychosis and mood episodes. Having undergone surgery on the unruptured intracranial aneurysm, the patient's psychiatric symptoms disappeared, and he maintained a stable mood during the 3‐year postoperative period. Discussion The case is indicative of the need to consider the possibility of organic brain lesions in patients with first episodes of psychiatric presentations.